2013
DOI: 10.1016/j.ijsu.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

To cool or not to cool: Evolution of the treatment of burns in the 18th century

Abstract: The 18th century represents a transitional period in evolution of surgery and burn treatment, a time just before major advances such as asepsis, burn excision and skin grafting, were to revolutionise surgical practice. The medical minds of this era first began to question the centuries of dogma and speculation that were at the heart of medicine. The evolution of the treatment of burns in this crucial time is reviewed from the perspective of two of the exceptional medical minds of that era John Hunter and James… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the nineteenth century, a number of oils, including Castor oil, were recommended as the first aid for burns. At the time, the oils were suggested for two reasons: their ability to exclude air from the burn and because of their accessibility, quick application was possible [ 81 , 82 ]. However, antioxidant activity has been demonstrated by methyl ricinoleate, ricinoleic acid, 12-octadecadienoic acid and methyl ester that are found in the seeds [ 80 , 83 ] and the astringent and antimicrobial actions of tannins, flavonoids, triterpenoids and sesquiterpenes also found in the seeds provide wound healing abilities, by promoting wound contraction and increasing the rate of epithelialisation [ 80 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the nineteenth century, a number of oils, including Castor oil, were recommended as the first aid for burns. At the time, the oils were suggested for two reasons: their ability to exclude air from the burn and because of their accessibility, quick application was possible [ 81 , 82 ]. However, antioxidant activity has been demonstrated by methyl ricinoleate, ricinoleic acid, 12-octadecadienoic acid and methyl ester that are found in the seeds [ 80 , 83 ] and the astringent and antimicrobial actions of tannins, flavonoids, triterpenoids and sesquiterpenes also found in the seeds provide wound healing abilities, by promoting wound contraction and increasing the rate of epithelialisation [ 80 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
“… 91 Cooling for the treatment of thermal injury has been advocated for at least a century, 92 and this recommendation stems from clinical experience from as far back as the time of Galen. 93 , 94 Cooling has been shown to significantly reduce burn injury severity and the likelihood of progression (also referred to as conversion ) of thermal injury in the hours to days after an initial insult. Clinically, a dose-response effect on the duration of cooling burns has been shown in a study of 2495 pediatric patients, with a threshold effect occurring at 20 minutes of cool running water ( Figure 4 ).…”
Section: Delayed Effects and Mechanisms Of Fistula Formationmentioning
confidence: 99%
“…Through our review of modern literature on ancient Mediterranean medicine, we found a lot of cross-referencing with a small number of reliable translations. Some descriptions only mention a spiritual or alternative medical therapy of burns in this time period [35]. The translation of ancient texts could shed new light on the treatment of burns in ancient times with a huge variety of strategies to treat burn wounds, to control infections but also to treat the patient during a burn-associated shock.…”
Section: Summa Summarummentioning
confidence: 99%